KAJIAN FEMINISME DALAM NOVEL BELALAH HAK-HAKMU PEREMPUAN DALAM ISLAM KARYA AYAAN HIRSI ALI - Putri Adelia Gunawan; Martono Martono; A. Totok Priyadi (Universitas Tanjungpura, 2021)
ABSTRACTThis study aims to describe the issue of gender injustice against women which is often an interesting topic of discussion in a novel. Common problems in this study are the oppression of Muslim women in western policies as well as the brutal oppression of religious culture. The theories used in the research are the theory of feminism, feminist literary criticism, the position of women in Islam, forms of women's struggle in Islam, and the study of literature in high school. The methods used are descriptive, qualitative research forms and use a feminist research approach. Data in the form of the position of Muslim women leaders, the form of struggle of Muslim women leaders, and implementation plans for learning Indonesian in the form of words, phrases, paragraphs, and quotations. The source of this research is the novel Belalah Hak-Hakmu Perempuan dalam Islam by Ayaan Hirsi Ali. The data collection technique used is a documentary study technique. Data analysis technique is a technique adopted from the theory of Miles, B. Mathew that is to analyze the position of Muslim women and the form of struggle of women. The results of data analysis in the form of the position of Muslim women in the family and in society in the form of the struggle of women in fighting for gender equality between men and women.Keywords: Feminism, novel